SIMULTANEOUS NITRIFICATION AND DIFFUSION IN SOIL .1. THE EFFECTS OF THE ADDITION OF A LOW-LEVEL OF AMMONIUM-CHLORIDE - Darrah, P; White, R; Nye, P (1985)
The mathematical model includes a kinetic model of nitrifier growth and activity, the adsorption equilibria of NH 4+ and soil acidity with the soil solid phase and the influence of other ions on the diffusion characteristics of each diffusing ion. Use of the model for predicting the penetration of NH 4+ and NO 3- into the soil is demonstrated. -from Authors